(untitled) (Bangladesh Journal of Nuclear Medicine, 2018)
Background: Renovascular hypertension is a secondary form of hypertension which occurs due to renal artery stenosis and is potentially curable. The gold standard for diagnosis of this condition is renal angiography which is rather invasive. Captopril renography on the other hand is an established technique used for more than three decades for accurate and non-invasive diagnosis of significant renovascular hypertension. At NINMAS captopril renography is also used to screen renovascular hypertension and has been a routine procedure since the mid- nineties. Aim: The aim of the present study is to reassess the value of captopril renography test after two decades of its use at NINMAS. Materials and Methods: This is a retrospective study of patients who underwent DTPA Captopril renography for evaluation of renovascular hypertension at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS). Divisional archive was searched and patient’s clinical record files were screened from January 2014- September 2015. In total thirty patients who had both baseline and post Captopril renography test during this period were selected and analyzed for the study. Results: Total 30 patients (male 21 and female 09, mean age 24± 5.5 years); were analyzed who completed both post Captopril and base line studies in two different days. The records showed that a baseline renal scintigraphy was performed with 370-444 MBq Tc-99m diethylene triamine pentaacetic acid (Tc-99m DTPA renogram). Scintigraphy was repeated within a week with 25-50 mg of oral Captopril given 60 min prior to the test. Among the 30 patients studied, normal post-captopril renogram was revealed in 08(26%) cases, abnormal findings in 12(40%) , the study was not sensitive in 06 (20%) due to gross parenchyma impairment (GPI) and no change was found in 04(14%) cases. On the basis of diagnostic criteria for gradation for renal arterial stenosis in 12 abnormal finding of Captopril study, the findings were, grade-1 in 06(20%), grade-2 in 05(17%) and grade -3 in 01(3%) cases. After assessing time activity curve, glomerular filtration and renal split function the probability assessment of renal arterial stenosis (RAS) among the abnormal Captopril studies (n=12) were determined and the high probability for RAS was found in 05 (42%), indeterminate in 03(25%) and low probability in 04(33%) cases. Conclusion: Captopril renography is a sensitive test for detection of RVH in patients in whom the renal function is as yet unimpaired. Even though our study is severely limited by the lack of confirmatory renal angiogram data, yet we can conclude that captopril renogram by itself is of considerable value since it can predict the functional significance of the stenosis. Therefore we conclude that captopril renography can add value to the diagnosis of RVH and should remain a method of choice even in this era of Doppler Ultrasound. Bangladesh J. Nuclear Med. 18(2): 131-134, July 2015